The economics of control : principles of welfare economics - Lerner, Abba P. (New York : A. M. Kelley, 1970)
This book highlights a theoretical framework solutions for economic problems, to conceptualize the economy collectively with an insightful modifications of thoughts.
Reprint of the 1944 ed.
includes index
sju 23/01/2019
Loans
Keywords: Welfare economics